Studi Perbandingan Konsep Tuhan Dalam Islam, Kristen dan Hindu - Pelealu, Nadia; Sahari, Gunar; Manu, Charisal B.S. (Vieka Wahana Semesta, 2025)
This research discusses the concept of God in the three major religions of Islam, Christianity and Hinduism, highlighting the differences and similarities in their theological teachings. Islam emphasizes the concept of Tawhid, which teaches the absolute oneness of God without partners. Christianity introduces the concept of the Trinity, which is one God in three persons: Father, Son, and Holy Spirit. Meanwhile, Hinduism has the concept of Brahman as the ultimate reality that is formless, but can be manifested in various deities, including the Trimurti (Brahma, Vishnu, and Shiva). This research uses a qualitative study method with a comparative theological approach, which aims to understand how the three religions define God as well as their doctrinal and philosophical implications. The main sources used include the holy books of each religion, namely the Qur’an, the Bible, and the Vedas, as well as related academic studies. Through this research, it is hoped to provide a broader understanding of the differences and common ground of the concept of God in the three religions as well as the importance of interfaith dialogue in building tolerance and social harmony.